A detailed experimental airfoil performance investigation using an equipped wind tunnel. (April 2020) - Hoseinzadeh, Siamak; Bahrami, Amin; Mirhosseini, Seyed Morteza; Sohani, Ali; Heyns, Stephan
Abstract: An experimental study is conducted to investigate the impact of different parameters on the performance of CFJ0025-065-196 airfoil. For this purpose, an equipped wind tunnel with the motor capacity of 7 kW as well as high-tech measuring instruments are employed, and the impact of attack angle on the average velocity profiles for different jet flow velocities, in addition to the self-similar velocity profiles for different attack angles, and the wake effect are found and discussed comprehensively. The experiments are done for five different values of the attack angle, which are 0, 5, 12, 20, and 25° as well three magnitude for the jet flow velocity, including 0, 19.7, and 32.2 m s −1 . According to the results, the attack angle in which the performance of the airfoil decreases has an upward trend when the jet flow velocity increases, and it reaches from 20 to 25° when jet flow velocity changes from 0 to 19.7 m s −1 . Moreover, increasing the attack angle from 0 to 12° makes the jet frountier wider whereas a downward trend happens by chaning the attack angle from 12 to 25°. Additionally, the higher the jet velocity is, the weaker wake stream has. Highlights: Performance of an airfoil is studied experimentally using an equipped wind tunnel. The experiments are done for five attack angles as well as three jet velocities. A direct relationship between the jet velocity and the stall angle is found. A reverse relationship between the jet velocity and the wake effect is found.